Dental maturity as an indicator of chronological age: validity of the demirjian method for dental age estimation when applied to Turkish children - Solak, Alev (My University, 2006)
Bu çalışmada Demirjian metodu kullanılarak 900 Türk çocuğunun (450 kız , 450 erkek) diş yaşları değerlendirildi. Hastalar, Marmara Üniversitesi Diş Hekimliği Fakültesi Ortodonti Anabilim Dalının arşiv dosyalarından derlendi.Çalışmada kullanılan çocukların doğum tarihleri 1984 ila 1999 yılları arasında değişmekteydi ve panoramik filmleri ise, hastalar 7 ila 15 yaşlarına geldiklerinde çekilmişti. Kızlar ve erkekler ayrı ayrı analiz edildi. Gözlemciler arasındaki hata derecesini ölçmek için Dt.Efthymiou’nun daha önceden analiz ettiği 85 panoramik film rastgele seçilerek tekrar analiz edildi ve Kappa hesaplandı.Gözlemcilerin dental skorları (DS) arasındaki güvenilirliği test etmek için intra-klas korelasyon katsayısı hesaplandı.Gözlemcilerin dental yaş (DA) değerleri arasındaki güvenilirliği ölçmek için ise t-test yapıldı.Dt.Solak’ın kendi ölçümleri arasındaki hata derecesini belirlemek için, 11 ay öncesinden kendi değerlendirdiği 70 panoramik film rastgele seçildi ve tekrar analiz edildi. Kronolojik yaş ve dental yaş arasında istatiksel olarak belirgin bir fark bulundu. Demirjian’ın analiz ettiği Fransız-Kanadalı çocuklara gore, erkekler ortalama 0,25 yaş ve kızlar ortalama 0,52 yaş daha ileride olduğu tespit edildi.Bu yüzden Fransız-Kanadalı standartlarının Türk çocuklarına uygun olmadığına karar verildi. Y = 100*{ eα +βx/ (1 + eα + βx )} lojistik denklemini baz alarak Türk populasyonu için yeni grafikler hesaplandı. Bu grafiklerin yanı sıra Demirjian metoduna gore hesaplanmış diş skorlarını Türk diş yaşına çevirmek için yeni tablolar oluşturuldu .

In this study the dental age of 900 Turkish children (450 girls and 450 boys) was evaluated according to the method of Demirjian. The sample was derived from the archive-files of the Orthodontic Clinic at Marmara University Dental School. They were born between years of 1984 and 1999 and were between 7 and 15 years of age at the time a panoramic radiograph (OPTG) was obtained. Girls and boys were analysed separately. To assess the degree of inter-observer error a random sample of 85 OPGs was selected from those previously analysed by Dt. Efthymiou and Cohen’s kappa was calculated.The inter-examiner reliability on the level of maturity scores (DS) was assessed with intra-class correlation coefficient (ICC). In order to test the inter-observer variation in dental age recordings, paired t-test was done. To assess the degree of intra-observer error a random sample of 70 OPGs was selected from those previously analysed by the author, approximately after 11 months of the initial analysis. A significant difference was found between chronological age and dental age. On average the boys were 0,25 years and the girls were 0,52 years ahead of the French-Canadian children analysed by Demirjian. Therefore, the French-Canadian standarts were not considered suitable for Turkish children. New graphs for the Turkish population were constructed using a logistic curve with the equation Y = 100*{ eα +βx/ (1 + eα + βx )} as a basis. In addition to the graphs, tables were produced which transfer the maturity scores calculated by the method of Demirjian into Turkish dental age.
Keywords: Ağız ve Diş Sağlığı_Türkiye; Ağız ve Diş Sağlığı, Çocuklarda